Improving emergency department trauma care in Fiji: Implementing and assessing the trauma call system. (28th January 2019) - Raj, Lavinesh Kumar; Creaton, Anne; Phillips, Georgina
Abstract: Objective: The trauma team process was recently implemented at the Colonial War Memorial (CWM) Hospital, Suva. This study audits the trauma call procedure at the hospital over a period of 12 months. Method: Retrospective descriptive study of trauma calls from August 2015 to July 2016 at CWM Hospital. Data relating to patient demographics, time of presentation, time to team assembly and time to computed tomography (CT) scan were extracted from the ED trauma call database. Disposition from the ED and status at hospital discharge was extracted from the hospital patient information system. Results: There were 38 trauma calls for 46 patients. Seventy‐two per cent were male. Eighty‐two per cent occurred when the CT radiographer was off site (16.00–08.00 h), including 47% that occurred between midnight and 08.00 h. Fifty‐two per cent of patients were intubated, 43% went to ICU, 26% went directly to the operating theatre, and 37% died. Benchmarks for time to trauma team assembly and time to CT scan were met in 50% of cases. Conclusion: This was a severely injured cohort of patients with a high mortality rate. The rate of missed calls was not assessed in this study. Time to CT scan could be improved with an onsite radiographer. Time to team assembly could be improved with trauma team training and early notification from pre‐hospital providers. There is a need to continue to monitor and refine the trauma call process and to extend data capture to measure injury severity and outcomes.